The Role of Contingent Workforce on the Vodafone-Oman Company Performance - Kawther Musabah Alghafri; Muadh Khalfan AlSiyabi; Bashaer Mabrook Albusaidi; Hafsa Mahmood Alhadi; Dr. Chandra Sekhara Reddy Kamireddy (International Journal of Engineering and Management Research, 2024)
Through contingent workforce, organizations can quickly add or remove their labor force in response to the changes in market demand. As per their seasonal demand requirements, most of the companies are gaining benefit through this flexible approach of recruiting the contingent employees. During the un-season or no-sales period, the management can easily remove these contingent employees and during the high-demand and peak-season period management can easily hire the new intake of contingent workers as per the situational requirement. This is how the management can reduce the burden of additional labor cost during their un-seasons and they are raising organizational performance and productivity during their peak seasons. Without making any long-term commitment the companies can test and use the skills and abilities of contingent workforce. Especially when the companies wish to expand, their branches to new territories and those who wish to start their new business with new products to test the market, these contingent workers are more profitable and cost saving strategies to the companies. The contingent workforce can also deliver the best of their wider pool of talents and skills in the organizations. With the rise of remote work and the gig economy, companies are taking quick decisions to hire the talent in their immediate geographical areas. This opens a world of possibilities for finding the right person for a specific job. Moreover, contingent workers often bring specific expertise and skills, which might be not available in the organization. This is an added advantage to the projects or initiatives, which have linked with specific and unique skills or knowledge. In many organizations, contingent workers are hired through third parties or consultants. In some companies, they are offering payment for number of hours worked or one lump sum amount after completion of total project work. Generally, these contingent workers will be recruited with no extra perks, appraisals and leaves as like as full time employees. Contingent workers have to perform as like as full-time workers even though they will be paid less comparatively with the full-time workers.